RHETORIC AND REALITY IN AIR WARFARE : THE EVOLUTION OF BRITISH AND AMERICAN IDEAS ABOUT STRATEGIC BOMBING, 1914-1945 - Biddle, Tami Davis (Princeton studies in international history and politics, 2004)
A major revision of our understanding of long-range bombing, this book examines how Anglo-American ideas about "strategic" bombing were formed and implemented. It argues that ideas about bombing civilian targets rested on--and gained validity from--widespread but substantially erroneous assumptions about the nature of modern industrial societies and their vulnerability to aerial bombardment. These assumptions were derived from the social and political context of the day and were maintained largely through cognitive error and bias. Tami Davis Biddle explains how air theorists, and those influenced by them, came to believe that strategic bombing would be an especially effective coercive tool and how they responded when their assumptions were challenged.